STUDI KUALITATIF: Peran Apoteker Dalam Edukasi Swamedikasi Pada Masyarakat Perkotaan - Mukriani, Mukriani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Background: Self-medication is a common practice in the community, especially in urban areas. Lack of understanding about drugs, dosages, and side effects often leads to irrational drug use. Pharmacists have a strategic role in providing education to the community to improve the safety and effectiveness of self-medication. Objective: This activity aims to qualitatively explore the role of pharmacists in self-medication education in urban communities, as well as identify obstacles and opportunities in its implementation. Method: This study was conducted through a qualitative approach with an in-depth interview method with 6 pharmacists and 10 community members in urban areas. Data were analyzed using a thematic approach. Results: It was found that pharmacists act as a trusted source of information on over-the-counter and OTC drugs, but their involvement is still limited due to workload, lack of time, and low public awareness of the importance of consulting with pharmacists. Conclusion: The role of pharmacists in self-medication education is very important but not optimal. Community-based interventions and supporting policies are needed so that self-medication education can run systematically and have a broad impact.